Evaluation of antimicrobial and antioxidant activities of alginate edible coatings incorporated with plant extracts - Lopes, Ana I. (2023)
Plant extracts (PEs) are natural substances that perform interesting bioactivities. However, they have some limitations. In this work, PEs from licorice, eucalyptus, sage, and thyme were produced and characterized. These extracts showed good bioactive properties. Alginate-based edible coatings and films incorporated with the extracts were produced and their antimicrobial and antioxidant properties were determined. The results showed that the coatings completely inhibited or reduced the growth of all bacteria (E. coli, P. aeruginosa, B. cereus, L. monocytogenes, and S. aureus), except the coating with sage extract. However, only the films incorporated with licorice and eucalyptus could inhibit the growth of Gram-positive bacteria and none of the films were able to inhibit Gram-negative bacteria. The film incorporated with sage extract was the one with the best antifungal property. All films possess a good antioxidant property (ABTS: 942.52–5654.62; DPPH: 1040.67–5162.93 Trolox equivalents (µM)/mg film). Based on the results, it is possible to conclude that alginate coatings and films with PEs present good bioactive properties and can potentially be used as new, biodegradable packages. However, further experiments need to be performed to assess their safety profile, and to prove that they can be a real alternative to traditional food packaging.